What makes theology theology? - Welker, Michael (Theology today, 2015)
Informed by a dialogue between the disciplines of law and theology on legal and theological dogmatics, the article describes nine levels that constitute theological normativity and weight. The first three levels deal with integrating concepts of God, with the historical, cultural, and theological weight of the biblical canon, and with confessional documents and multi-loci dogmatics, respectively. These are central parts of the spectrum. The ecclesial, academic, and contextual-ethical responsibilities (integral to truth- and justice-seeking communities), the professional ethos and the institutional frameworks are equally important. Finally, the radiations of these six levels with individual piety and a shared living faith and the reverse shaping powers of practiced religious experience are all indispensable for the enterprise of theology.